Behavior assessment for non-communicable disease prevention using the health belief model - Addellia Yoma Hastani; Helfi Agustin; Hary Budiman; Ezza Addini (Universitas Ahmad Dahlan, 2023)
Background: Germacis is a community-based program educating and facilitating people to adopt a healthy lifestyle in Jogokaryan hamlet, Yogyakarta. It includes doing physical activities with groups, doing health checks, not smoking in the house or at community meetings, and replacing snacks with fruit. This study aims to evaluate whether the program positively impacts community behavior by assessing perceptions and practices of healthy lifestyles based on participation after the program has been implemented for two years. Methods: This quantitative research with a cross-sectional approach uses the perception assessment of the health behavior model (HBM). The population was 165 people, and the sample was 54 from the Hamlet number 36 at Jogokariyan sub-district, Yogyakarta. This research collected primary data using a 4-Likert scale questionnaire. Data were analyzed using the chi-square test. Results: There is a relationship between active participation in activities and perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and prevention behavior. There is no relationship between participation and self-efficacy. Our result shows the p-value of the 5 HBM constructs is 0.01; 0.00; 0.00; 0.03; 0.34, and 0.00 for perceived susceptibility, severity, benefits, barriers, self-efficacy, and cues to section; respectively. Conclusion: Program managers should consider sanctions to encourage self-efficacy in behavior, especially for active smokers; they must not smoke at home or in community meetings.